KEDUDUKAN GADAI SYARIAH (RAHN) DALAM SISTEM HUKUM JAMINAN INDONESIA - Budiman Setyo (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Rahn according to Islamic Law is a guarantee institution used in Syariah Bank. Based on the existence, Rahn legal construction has similar traits to the legal construction of pand (Gadai) according to Civil Code. Those traits are consisting of an accessory transaction for the main transaction as a monetary transaction, an moveable object for its guarantee, a principle of in- bezitstelling, a preferent creditor for payment for its debt. Therefore, all regulations for pand (gadai) can be applied to Rahn with analogical interpretation.Keywords : Rahn, pand, Islamic Law